2008
DOI: 10.1021/la802287s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight on the Morphology of Polystyrene/Poly(methyl methacrylate) Composite Particles Prepared by the Solvent Evaporation Method

Abstract: The effect of molecular weight on the morphology of polystyrene (PS)/poly(methyl methacrylate) (PMMA) composite particles was investigated. PS/PMMA composite particles with different molecular weights (M*=MwPS+MwPMMA)/2 approximately 2x10(4)-1x10(6) g.mol(-1)) were prepared by the release of toluene (T) from PS/PMMA/T (1/1/24, w/w/w) droplets dispersed in an aqueous solution of polyoxyethylene nonylphenyl ether nonionic surfactant (Emulgen 911). As T evaporated, the spherical droplets phase separated, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 53 publications
2
63
0
2
Order By: Relevance
“…The w parameter between PS and toluene depends on the polymer concentration. These effects were not considered in the calculation of interfacial tensions, and as assumed previously, 38 the w parameter was treated as constant in the current study. Figure 1 shows g PS-T/Surf-w and g HD-T/Surf-w with various types of surfactants as functions of w PS and w HD .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The w parameter between PS and toluene depends on the polymer concentration. These effects were not considered in the calculation of interfacial tensions, and as assumed previously, 38 the w parameter was treated as constant in the current study. Figure 1 shows g PS-T/Surf-w and g HD-T/Surf-w with various types of surfactants as functions of w PS and w HD .…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38] It was revealed that the particle morphology could be controlled by tuning the interfacial tensions by varying the types of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Vor kurzem wurden PS/PMMAJanus-Strukturen durch Dispergieren von in Toluol gelçstem PMMA und PS in einer wässrigen Lçsung des Tensids Polyoxyethylennonylphenylether (E911) hergestellt (J-1, Schema 1 a). [57] Während das Toluol verdampft, trennen sich die [58] Axialsymmetrische Janus-Verbundtrçpfchen aus PS-und Abbildung 1. Synthese anisotroper hantelfçrmiger Partikel mit dem Impfpolymerisationsverfahren.…”
Section: Weiche Janus-strukturenunclassified
“…[30] As the solvent evaporates, spherical droplets phase separate, and Janus particles were obtained that could be visualized by scanning electron microscopy (SEM; Figure 1). Interestingly, the morphology varies in a characteristic manner with the molecular weights of the polymers.…”
Section: From Homopolymers To Janus Particlesmentioning
confidence: 99%